Analisis Perlindungan Konsumen dalam Transaksi E-Commerce di Kabupaten Kuningan - Ulfa Habibah; Vaskal Maulana; Zahra Dwi Putri; Zea Septiani (Letterlijk, 2024)
Consumer protection in e-commerce transactions is very important in the current digital era. With the rapid development of internet technology, buying and selling transactions via e-commerce platforms have become part of everyday life. However, there are limitations in legal regulations and limited consumer rights in the Consumer Protection Law No. 8 of 1999 and the Information and Electronic Transactions Law (UUITE) have created problems in legal protection for consumers. This research discusses legal protection for consumers in e-commerce transactions, with a focus on the Consumer Protection Law and UUITE as the legal basis that regulates consumer protection. The research results show that legal protection for consumers in e-commerce transactions needs to be expanded and clarified to ensure legal certainty and protection of consumer rights in e-commerce transactions. Keywords : Consumer Protection, E-commerce Transactions, Consumer Protection Law, Information and Electronic Transactions Law.